Propagation and vertical structure of the tidal flow in Nares Strait - Davis, P; Johnson, H; Melling, H (American Geophysical Union, 2019)
The southward freshwater flux through Nares Strait is an important component of the Arctic's freshwater budget. On short time scales, flow through the strait is dominated by the tides, and tidal dynamics may be important for the magnitude of the freshwater flux over longer periods. Here we build upon our existing knowledge of the tides in the region by exploring their propagation and vertical structure using data from four bottom‐mounted Acoustic Doppler Current Profilers deployed in Nares Strait between 2003 and 2006. We observe that propagating barotropic semidiurnal tidal waves interact to create a standing wave pattern, explaining the abnormally large tidal amplitudes that are observed in this region. In the along‐strait direction, semidiurnal tidal currents exhibit strong variations with depth. In contrast, the diurnal tides propagate northward through the strait as progressive waves, and the tidal currents are broadly depth invariant. Proximity of Nares Strait to the semidiurnal critical latitude and the topographical restriction imposed by the steep side wall of Ellesmere Island are primary drivers behind the observed vertical variability. In the upper part of the water column, baroclinic activity increases the tidal current amplitude by up to 25%. In the across‐strait direction, a two‐layer structure exists in both the diurnal and semidiurnal tidal flow, with a phase lag of approximately a quarter of a tidal cycle across the strait for the semidiurnal tide. Our results suggest that strong vertical motion exists against the side walls of Nares Strait, as the across‐strait flow interacts with the steeply sloping bathymetry.